2012
DOI: 10.1038/jid.2011.414
|View full text |Cite
|
Sign up to set email alerts
|

Sema4D, the Ligand for Plexin B1, Suppresses c-Met Activation and Migration and Promotes Melanocyte Survival and Growth

Abstract: Semaphorins are secreted and membrane bound proteins involved in neural pathfinding, organogenesis, and tumor progression, through Plexin and neuropilins receptors. We recently reported that Plexin B1, the Semaphorin 4D receptor, is a tumor suppressor protein for melanoma, in part, through inhibition of the oncogenic c-Met tyrosine kinase receptor. In this report we show that Sema4D is a protective paracrine factor for normal human melanocyte survival in response to ultraviolet irradiation, that it stimulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 48 publications
(69 reference statements)
0
40
0
5
Order By: Relevance
“…Paracrine and autocrine factors regulate melanocyte function and play a role in transformation of melanocytes to melanoma (Haass et al, 2004;Villanueva and Herlyn, 2008). We have shown that melanocytes express the neural guidance receptor Plexin B1, which regulates melanocyte survival and proliferation, through binding to its ligand, Semaphorin 4D (Sema4D) (Soong et al, 2012). Sema4D is expressed by keratinocytes and melanocytes, thereby functioning as an autocrine and paracrine factor (Soong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Paracrine and autocrine factors regulate melanocyte function and play a role in transformation of melanocytes to melanoma (Haass et al, 2004;Villanueva and Herlyn, 2008). We have shown that melanocytes express the neural guidance receptor Plexin B1, which regulates melanocyte survival and proliferation, through binding to its ligand, Semaphorin 4D (Sema4D) (Soong et al, 2012). Sema4D is expressed by keratinocytes and melanocytes, thereby functioning as an autocrine and paracrine factor (Soong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Muitos trabalhos têm estudado o papel de CD100 no sistema nervoso (MOREAU-FAUVARQUE et al, 2003, YAMAGUCHI et al, 2011, em crescimento e angiogênese tumorais (BASILE et al, 2006, SIERRA et al, 2008, CH'NG e KUMANOGOH, 2010, GABROVSKA et al, 2011, SOONG et al, 2011, YANG et al, 2011 e em osteogênese. No sistema nervoso central foi demonstrado que CD100, em cérebro embrionário de camundongos, induz um colapso dos cones de crescimento de axônios (FURUYAMA et al, 1996, SWIERCZ et al, 2002, em cérebro pós-natal inibe o desenvolvimento de oligodendrócitos (YAMAGUCHI et al, 2011) e em adultos é expresso por oligodendrócitos e mielina e após uma lesão no SNC inibe a regeneração axonal (MOREAU-FAUVARQUE et al, 2003).…”
Section: Cd100 Seus Receptores E O Sistema Imuneunclassified
“…De fato, camundongos CD100 e plexina B1 negativos mostraram um fenótipo de osteosclerose devido ao aumento da formação óssea (NEGISHI-KOGA et al, 2011). Em tumores, CD100 tem efeito de supressão da proliferação de melanoma (SOONG et al, 2011). CD100 expresso em queratinócitos ao se associar a seu receptor Plexina B1 expresso por melanócitos, promove a sobrevivência e proliferação dos melanócitos humanos na pele (SOONG et al, 2011).…”
Section: Cd100 Seus Receptores E O Sistema Imuneunclassified
See 2 more Smart Citations